Indian Outward Foreign Direct Investment into Europe - Wancio, Agata (Indyjskie inwestycje bezpośrednie w Europie, 2010)
The paper discusses Europe's significance as a localization for Indian direct investments. The special attention is paid to the period after 2000 because then an explosion of direct investment from India into Europe was observed. The vast majority of FDI projects are concentrated in the EU 15. Especially dynamic growth has occurred in case of Indian FDI into the UK, mainly because of large Indian M&A purchases undertaken there. Besides the UK, the main host countries for Indian FDI arc Germany, France, Italy, the Netherlands, Norway, Spain, Ireland and Russia. Indian multinationals are engaged in Europe in various sectors with a strong presence of companies from IT services, automobile, life sciences (mainly pharmaceuticals and biotechnology) and metals industry.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 274-283
Keywords: India; multinationals; mergers and aquisitions (M&A); foregin direct investment (FDI); Europe